Associate Professor Candidates Who Don’t Take LIS Education - Hasan S. Keseroğlu (Türk Kütüphaneciliği)
In recent years, the number of those who want to become associate professor in the field of library and information science has increased. It is inapprehensible to take the title of associate professor -which is one of the most important stages of academic life- from an irrelevant subject. In the field of LIS, it will be important to make some joint decisions in this regard. Having a common attitude in this regard will create some drawbacks for tomorrow; at least I think that it will be meaningful for those who will apply as candidates for associate professor in this field to know the criteria. Most importantly, in an environment where the qualitative value of universities becomes unclear, the field of Information and Document Management will be away from this complexity for a while.